2021
DOI: 10.15446/rcp.v30n2.88781
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Strategies for Reading Comprehension in Middle School

Abstract: In this study, we investigated the relationships among achievement goals, self-efficacy, reading strategies, and the self assessment of performance in 47 Middle School students with control of the variable’s history of repetition, school year, and age. The differences in the students’ self-assessment regarding the practice of recreational reading were also analyzed. The students responded to three scales of the Multidimensional Battery of Reading Comprehension Self-Regulation. Statistically significant correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, the low correlations indicated that reading strategies are not the only one that affect students reading achievement. EFL teachers also need to consider other factors, such as students' reading efficacy, reading motivation, reading frequency, linguistic knowledge (Ferraz et al, 2021;Kassem & Alqahtani, 2023;Kyung Ja Kim, 2015;Taladngoen et al, 2020). Student who has a better perception of his reading ability thinks more positively about English reading and spends more time in reading (Kyung Ja Kim, 2015).…”
Section: Table 4 Pearson Product Moment Correlation Resultsmentioning
confidence: 99%
“…However, the low correlations indicated that reading strategies are not the only one that affect students reading achievement. EFL teachers also need to consider other factors, such as students' reading efficacy, reading motivation, reading frequency, linguistic knowledge (Ferraz et al, 2021;Kassem & Alqahtani, 2023;Kyung Ja Kim, 2015;Taladngoen et al, 2020). Student who has a better perception of his reading ability thinks more positively about English reading and spends more time in reading (Kyung Ja Kim, 2015).…”
Section: Table 4 Pearson Product Moment Correlation Resultsmentioning
confidence: 99%
“…In spite of numerous studies on L2 motivation, most target learners of English as a L2, while not many studies focus on learners of other languages as a L2 (Csizér & Kormos, 2008; Ferraz et al, 2021; Liu, 2017, 2020; Ruan et al, 2015; Wesely, 2009). It is the same with learners of Chinese as a L2 (Gong et al, 2020b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Coupled with the complex nature of language learning and the ongoing interaction of various variables during the process, there is a call for more research on the interaction between L2 motivation and the learning environment to better understand its dynamic nature. Moreover, as reviewed below, most current L2 motivation research targets learners of English as a L2, while not much research targets learners of other languages as a L2 (Csizér & Kormos, 2008; Ferraz et al, 2021; Wesely, 2009). Even less such research has been done on learners of Chinese as a L2 (Cai & Zhu, 2012; Gong et al, 2020b; Liu, 2017, 2020; Ruan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%